POTENSI RUMPUT LAUT DI PANTAI BAYAH, KABUPATEN LEBAK, BANTEN SEBAGAI ANTIBAKTERI Escherichia coli - Triastinurmiatiningsih, Triastinurmiatiningsih; Haryani, Tri Saptari (LPPM Universitas Terbuka, 2008)
Antibacterial potency of some seaweed against Escherichia coli has been known. The aim of this research is to know the species of seaweeds from Bayah beach Lebak Banten which may be used as antibacterial against Escherichia coli. Twenty one seaweed species samples from Bayah Beach Lebak Banten were exstracted by organic solvent of absolute methanol according to Espeche, Fraile, and Mayer (1984) and Darusman, Sayuti, Komar & Pamungkas (1992) methods. The antibacterial activities were examined by means of Kirby-Bauer or diffusion method. The results showed antibacterial activities occur from the extract of Boodlea composite, Chaetomorpha crassa, Ulva fasciata, Sargassum crustaefolium, Padina australis and Halimeda gracilis. Sofar, Padina australis extract had shown better inhibitory activities than others.